The effects of differences in trophectoderm biopsy techniques and the number of cells collected for biopsy on next‐generation sequencing results - Yamato Mizobe; Yukari Kuwatsuru; Yuko Kuroki; Yumiko Fukumoto; Mari Tokudome; Harue Moewaki; Mia Watanabe; Tokiko Iwakawa; Kazuhiro Takeuchi (Reproductive Medicine and Biology, 2022)
Abstract Purpose To examine how differences in trophectoderm biopsy techniques affect the frequency of mosaic embryos and sequencing results. Methods We examined differences in next‐generation sequencing (NGS) analysis results among operators or according to biopsy technique. Additionally, we determined the cut‐off for the number of collected cells to predict the occurrence of mosaicism. We collected cells according to the cut‐off value and examined whether there was a difference in the NGS analysis results between the pulling and flicking methods. Results There was no difference in the NGS analysis results among the operators. Regarding re‐biopsy, changes in the mosaic were observed in all specimens. The cut‐off value for the number of collected cells was five, and when more than five cells were collected, there was no difference in the NGS analysis results between the two methods. Conclusions We demonstrated that if trophectoderm biopsy techniques and NGS are stable, the cell collection location has a greater effect on NGS results than the biopsy technique.